Risk Factors for Thrombosis in Simultaneous Pancreas-Kidney Transplants Performed Over Ten Years at Westmead Hospital. (July 2018) - Shahrestani, Sara; Spike, Erin; Hort, Amy; Gibbons, Thomas; Hitos, Kerry; Lendzion, Rebecca; Robinson, Paul; Pleass, Henry C; Kable, Kathy; Lam, Vincent; de Roo, Ronald; Yuen, Lawrence; et al.
Abstract : Introduction: Simultaneous pancreas-kidney (SPK) transplant remains the gold standard treatment renal failure secondary to Type 1 diabetes. Thrombosis in the early post-transplant period is an early complication with devastating outcomes, including multiple procedures, return to the operating theatre and in many cases graft loss. This is the first study to comprehensively examine the potential role of numerous risk factors for thrombosis in SPK transplant recipients. Materials and Methods: We reviewed all simultaneous pancreas-kidney transplants (SPK) performed at our institution over the past 10 years (2008-2017) including 235 patients. Risk factors for thrombosis including donor factors (age, gender, BMI, smoking status, hypoxia in cause of death), recipient factors (age, gender, BMI, hypertension, diabetes, vascular disease and smoking status) and operative factors (vasopressor use, blood pressure, ischemic time, anastomotic time, fluid boluses, arterial or venous grafts) were examined. Adjusting for possible confounders, a multivariate logistic regression model was used to assess the risk and predictors of thrombosis using SPSS v. 22.0. Results and Discussion: Of the 235 patients, 41 (17.4%) experienced thrombosis of the pancreas graft. Of the total patients, 16 (6.8%) lost the pancreas graft as a consequence of the thrombosis. The risks of thrombosis increases by 25.6 fold in male donors (compared to females) (OR: 25.6; 95% CI: 2.2-303.1; P=0.01). The presence of hypoxia increases the odds of thrombosis by as much as 4.0 fold (OR: 4.0; 95% CI: 0.8-21.4; P=0.102). The age of the donor plays a significant role. Patients between 26 to 35 years have a 2.7 fold increased risk compared to those less than 20 years (OR: 2.7; 95% CI: 0.4-18.7; P=0.32). This risk almost doubles in donors >36 years (OR: 5.3; 95% CI: 0.6-47.3; P=0.14). A recipient between the age of 37 to 42 years is at 10.6 times greater risk of thrombosis compared to those <36 years (OR: 10.6; 95% CI: 1.4-79.2; P=0.02). Conclusions: Results of this work suggest that careful selection of donors for pancreas transplantation is paramount to reducing the risk of thrombosis. Donor gender, age, and cause of death can be used to decide which donors are at highest risk. Female donors, younger donors and those with a cause of death that does not involve hypoxia can be considered the lowest risk donors. In higher risk donors, the use of interventions that reduce the risk of thrombosis or more careful vigilance may aid prevention of graft loss due to this challenging complication.